Influence of Aerobic Exercise on Functional Capacity and Maximal Oxygen Uptake in Patients With Parkinson Disease: A Systematic Review and Meta-analysis - Barbieri, Ricardo Augusto; Barbieri, Fabio Augusto [UNESP]; Zelada-Astudillo, Nicolle; Moreno, Vinicius Christianini [UNESP]; Kalva-Filho, Carlos Augusto [UNESP]; Zamunér, Antonio Roberto (Elsevier, 2025)
Objective: To determine the effects of aerobic training in randomized controlled clinical trials on functional capacity, motor symptoms, and oxygen consumption in individuals with Parkinson disease (PD) through a systematic literature review and meta-analysis. Data Sources: PUBMED, Web of Science, CINAHL, SciELO, and Medline databases were searched to identify published studies until September 2023. Study Selection: Randomized controlled clinical trials that evaluated the long-term effect of aerobic exercise in individuals with PD were included. Data Extraction: Two independent reviewers extracted the data and assessed the risk of bias and the Grading of Recommendation Assessment, Development, and Evaluation. In case of disagreement, a third reviewer was consulted. Data Synthesis: Thirteen studies were included in the systematic review, and the number of participants was 588 with an average age of 66.2 years (57-73y). The study's exercise intervention lasted between 6 and 70 weeks, with most studies lasting 10-12 weeks, with 3 sessions per week and an average duration of 47 minutes per session. The meta-analysis revealed that aerobic exercise is effective in enhancing maximal oxygen uptake (standardized mean difference, SMD 0.42 [95% CI, 0.18, 0.66; P=.0007]) and functional capacity (SMD 0.48 [95% CI, 0.24−0.71; P<.0001]). In addition, aerobic exercise can reduce the motor-unified Parkinson disease rating scale (mean difference−2.48 [95% CI, −3.16 to −1.81; P<.00001]) score in individuals with PD. Conclusions: Aerobic exercise training conducted 2-3 times a week, with different intensities (low to high), can be an effective intervention for enhancing functional capacity, maximizing oxygen uptake, and reducing the UPDRS scores in individuals with PD.
Keywords: Aerobic exercise; Functional capacity; Maximal oxygen uptake; Meta-analysis; Parkinson disease; Rehabilitation